STRATEGI PEMASARAN PENGEMBANGAN INVESTASI BISNIS KOMPONEN BAHAN BAKU PADA PT. EGA NUSANTARA - Eko Yogy Prasetyo; AEP RUHANDI (Universitas Muhammadiyah Tangerang, 2019)
PT. Ega Nusantara is one of the medium voltage panel maker companies in Indonesia. Where the majority of products are used by PT. PLN throughout Indonesia. PT. Ega Nusantara seeks to improve its competitiveness by adding new products outside the panel, namely current transformers, voltage transformers, bushings, capacitive deviders, insulators and load break switches. The whole component is a panel supporting component made from epoxy resin. To expand, a study of marketing strategies is needed using SWOT analysis and identifies the company's internal and external environmental factors that influence marketing strategies. Indonesia's current economic growth requires the support of reliable energy supplies including electricity. Electricity needs will increase in line with economic development and population growth. Based on the RUPTL (Electricity Supply Business Plan) PT. PLN, Indonesia have’t get the electricity of all regions could become potential investment in the electricity sector. The electrification ratio up to 2016 was 91.16%. When compared to Singapore it's already 100%, Brunei Darussalam 99.7%, Malaysia 99.0%, Thailand 99.3%, and Vietnam 98.0%. In addition to the condition of the electrification ratio that has not reached 100%, the condition of the electricity supply in the national electricity system also reflects the imbalance between supply and demand, with these conditions, of course, there are still opportunities for investors to participate in electricity supply businesses.